Legal Culture and the Dynamics of Religious Interaction in Ritual Practices among Interfaith Marriage - Muchimah; Jahar, Asep Saepudin; Hamdani; Fajarini, Ulfah (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This study examines the legal culture dealing with the interaction of religious practices and rituals among interfaith couples in Purwokerto, Central Java, emphasizing the social and legal dynamics influencing family life. In Indonesian society, interfaith marriage presents a complex issue, intersecting between state legal regulations and religious doctrines. By using qualitative methods through in-depth interviews and analysis of legal documents, this research delves into how interfaith couples navigate their daily lives, compromise the religious differences, and adapt to the prevailing legal framework. Legal culture component in legal system, comprising values and attitudes that influence the operation of the law, this research argues that legal culture significantly influences the practices in n t both social and and religious rituals, struggling the efforts to maintain household harmony. The issuance of Supreme Court Circular (SEMA) Number 2 of 2023 gave impact to the comprehensive legal interpretation and adaptation. This study demonstrates of understanding the interrelation of law, religion, and social practices within Indonesia’s religious pluralism and its implications for the legal acknowledgment and spiritual lives of interfaith couples.